A Legal Inquiry into the Sustainability of the West African Gas Pipelines Project - KINGSTON, Kato Gogo; NWAUZI, Linus O. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
The history of cross border and transit oil and gas pipelines suggests a tendency to cause conflict and discrepancy which do result in the interruption of output. It is inviting to link this to poor political relations between neighbor countries. The concern with transit and cross-border pipelines has a significant legal implication. The intricacies of the legal and regulatory frameworks for the regional pipeline project together with the issues of multiple jurisdictions require well-articulated dispute settlement regime. This is necessary in view of the disorganized judicial systems throughout the West African region – disputes in the Nigerian and Ghanaian courts have the tendency to drag on for years without determination. In the face of the disparity in the legal systems of the contracting nations, this study critically examined the legal sustainability of the West African Gas Pipeline Project.